The Role of IoT in Improving the Efficiency and Quality of Automated Production in Industry 4.0: A Bibliometric Review - Loso Judijanto; Etika Purnamasari; Ade Suhara; Nanny Mayasari; Khamaludin Khamaludin (Westscience Press, 2024)
This bibliometric review explores the dynamic field of talent management, focusing on the integration of digital technologies and their impact on modern organizational practices. Using VOSviewer for a systematic analysis, the study maps the evolution of key themes and trends over recent years, highlighting the central role of talent management and the significant shift towards incorporating advanced technologies like IoT, data analytics, and machine learning. The findings reveal a transformation from traditional practices to a more strategic, data-driven approach that aligns talent management with competitive business objectives. This transition not only enhances operational efficiencies but also supports a culture of continuous improvement and innovation. The study also addresses the challenges and future directions in leveraging technology for effective talent management, providing insights that are crucial for organizations aiming to maintain a competitive edge in a rapidly evolving digital landscape.